In vitro antimicrobial activity of AH Plus, EndoREZ and Epiphany against microorganisms - Maekawa, Lilian [UNESP]; Nassri, Maria Renata; Ishikawa, Camila; Martins, Carolina; Chung, Adriana [UNESP]; Koga-Ito, Cristiane [UNESP] (Wolters Kluwer, 2012)
Objective : The aim of the present study was to evaluate the antimicrobial activity of endodontic sealers against microorganisms. Materials and Methods : The agar diffusion method was used. A double base layer of Mueller Hinton agar was done. The microorganisms used were: Candida albicans, Enterococcus faecalis, Escherichia coli and Staphylococcus aureus. The wells were obtained by removing a standardized portion of the agar. After the distribution of the sealers, Petri plates were incubated for 24 h. Inhibition halos formed around the wells were measured. Results : Epiphany did not show any antimicrobial activity on the tested microorganisms (without inhibition halo). The AH Plus showed the greatest inhibition halo on C. albicans followed by EndoREZ on S. aureus. EndoREZ also showed greater inhibition halo in comparison to AH Plus on E. faecalis and E. coli. Conclusion : It could be concluded that AH Plus and EndoREZ showed antimicrobial activity against all the tested microorganisms. No antimicrobial activity was observed for Epiphany.
Keywords: Agar diffusion method; endodontic sealers; microorganisms